Antonio Gramsci and the search for the "educational principle" - Meta, Chiara (International Gramsci Journal, 2025)
This work intends to explore the theme of education in the thought of Antonio Gramsci, in the light of an ‘integral’ approach to his intellectual biography. The first part of the paper will reconstruct the centrality of the ‘educational theme’ in the young Gramsci, starting from the years of his university studies up to the birth of ‘integral journalism’. This part of the work will also highlight the influence exerted on the young Gramsci's education by the early 20th century avant-garde, French spiritualism (Bergson, Sorel) and Benedetto Croce. In the second part, the work will examine the Prison Notebooks, and an attempt will be made to reconstruct the link between the lemma ‘philosophy of praxis’ and education.